2017
DOI: 10.1159/000464410
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Features and Treatment Outcome of Malignant Pleural Mesothelioma

Abstract: Background: Malignant pleural mesothelioma is a problematic condition due to poor prognosis and difficulties in management. We evaluated the treatment and outcome of 378 mesothelioma patients referred to 6 Italian Oncology Departments. Methods: Demographic and clinical data were collected. Treatment was assessed in terms of chemotherapy (line of treatment, pemetrexed-based regimen, other therapies), surgery, and radiotherapy. Response to therapy, progression-free survival, and overall survival were evaluated. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…While no significance was found in the treated group, only 14.7% were women, hence they were potentially underrepresented. Some previous studies have suggested that female gender is associated with improved OS in MM patients, while others did not [11,12,23]. This study indicates that female gender is a significant protective factor in BSC patients, although the mechanisms responsible for this are unclear [24].…”
Section: Prognostic Factors Of Survivalmentioning
confidence: 54%
See 1 more Smart Citation
“…While no significance was found in the treated group, only 14.7% were women, hence they were potentially underrepresented. Some previous studies have suggested that female gender is associated with improved OS in MM patients, while others did not [11,12,23]. This study indicates that female gender is a significant protective factor in BSC patients, although the mechanisms responsible for this are unclear [24].…”
Section: Prognostic Factors Of Survivalmentioning
confidence: 54%
“…Age was not a significant prognostic factor in either group. Other studies found that age was a significant factor [11,23]. However, they did not adjust for PS, and PS does not necessarily to correlate to age, as seen in other patient populations with cancer [27].…”
Section: Prognostic Factors Of Survivalmentioning
confidence: 90%
“…There are other treatments as PD with intraoperative intracavitary hyperthermic CT, although more studies need to support and analyze concerning the long-term results [105][106][107][108][109][110][111][112][113]. The majority of studies that evaluate the trimodal approach are retrospective reviews [114][115][116][117][118][119]. Since 2007, a multicentric clinical trial demonstrated that iCT plus EPP is feasible [41] showing an OS of 23 months compared with patients not treated with surgery with a survival of 19.8 months [41].…”
Section: Bimodal and Trimodal Therapy In Mpmmentioning
confidence: 99%
“…However, the results of these have been disappointing [4][5][6]. Pemetrexed in combination with cisplatin is currently used as the standard first-line therapy for unresectable mesothelioma, yielding an overall survival time of 12.1 months [7].…”
mentioning
confidence: 99%
“…Most MM patients have unresectable disease, and therefore, different anticancer drug regimens have been tested in clinical trials. However, the results of these have been disappointing [4–6]. Pemetrexed in combination with cisplatin is currently used as the standard first‐line therapy for unresectable mesothelioma, yielding an overall survival time of 12.1 months [7].…”
mentioning
confidence: 99%